Pengaruh Profitabilitas, Firm Size, Leverage, Dan Net Working Capital Terhadap Cash Holding - Vidyarto Nugroho, Karen Darmawan, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This research was conducted with the aim of obtaining empirical evidence of the effect of Profitability, firm size, leverage, and Net Working Capital on Cash Holding. Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period are the subjects that will be used in this study. The test was carried out on 258 samples of data from 86 samples of manufacturing companies that had been processed using the purposive sampling technique. EViews ver 12.0 program will be used for data processing. The research conducted shows that profitability and Firm Size do not have a significant positive effect on Cash Holding, Leverage has a significant positive effect on Cash Holding, and Net Working Capital has a significant positive effect on Cash Holding.